Measurements of anomalous cosmic rays from the WIND spacecraft over 1994–2021. Issue 4 (24th November 2022) - Fu, Shuai; Zhang, Xiaoping; Zhao, Lingling; Wang, Ming; Shang, Wensai; Luo, Pengwei
ABSTRACT: Observations provide direct evidence for a sustained decline in solar activity since the 1980s, with the minimum between solar cycles 24 and 25 ( P 24/25 ) reaching its deepest trough in the past hundred years. In response to the reduced solar modulation, low-energy (24/25, while anomalous cosmic rays (ACRs) show very inconsistent variations with GCRs. To better understand the long-term ACR variations, we revisit the 6.0–13.4 MeV nuc −1 oxygen measurements from the WIND/LEMT instrument over 1994–2021, with particular interests to the recent three solar minima: P 22/23 (solar magnetic polarity A > 0), P 23/24 ( A < 0), and P 24/25 ( A > 0). We find that the peak ACR intensities in P 24/25 are ∼20 per cent lower than those in P 22/23 but ∼48 per cent above those in P 23/24 . Additionally, for a specified heliospheric current sheet (HCS) tilt angle, the GCR intensities in P 24/25 are inferred to be significantly higher than those in P 22/23 (both are in A > 0 cycles), whereas the ACR intensities in P 24/25 are close to those in P 22/23 . These results indicate that large variability in ACRs exists not only between opposite-polarity cycles, but also between different cycles of the same polarity, and ACRs may be more sensitive to varying HCS compared to GCRs. We speculate that variations in the ACR source intensity may be a key to understanding the ACR–GCR discrepancies. This is the first time for such a long-term study being possible with the same instrument.